EFFECT OF JOB ENRICHMENT AND DIRECT FINANCIAL COMPENSATION ON JOB SATISFACTION WITH MOTIVATION AS AN INTERVENING AT BANK BRI BRANCH OFFICE TENGGARONG - Puji Lestari; Doddy Adhi Mursandi; Siti Maria (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The development of Indonesia's financial industry has a suitable image from the perspective world; one of them is Bank Rakyat Indonesia, which has the highest rank in the most extensive company category in Indonesia with 347 out of 2000 companies in the world. (Andrea Murphy, Hank Tucker, 2020). To get this achievement, indeed not be separated from one of the company employees' essential aspects. The purpose of this study was to determine the effect of job enrichment and direct financial compensation on job satisfaction and whether Motivation also has an indirect relationship with job satisfaction. The data analysis technique used was variant-based structural equation modeling with has research method using partial least square. This research shows that job enrichment and direct financial compensation have simultaneously a significant positive to job satisfaction, but for motivational construct has contributed positively but does not experience a significant to job satisfaction. And to motivation dimension, job enrichment has a significant positive effect on Motivation, but job satisfaction has a positive but insignificant effect on Motivation